Bcl-2 Antiapoptotic Family Proteins and Chemoresistance in Cancer - Maji, Santanu; Panda, Sanjay; Samal, Sabindra K; Shriwas, Omprakash; Rath, Rachna; Pellecchia, Maurizio; Emdad, Luni; Das, Swadesh K; Fisher, Paul B; Dash, Rupesh (Advances in cancer research, 2018)
Cancer is a daunting global problem confronting the world's population. The most frequent therapeutic approaches include surgery, chemotherapy, radiotherapy, and more recently immunotherapy. In the case of chemotherapy, patients ultimately develop resistance to both single and multiple chemotherapeutic agents, which can culminate in metastatic disease which is a major cause of patient death from solid tumors. Chemoresistance, a primary cause of treatment failure, is attributed to multiple factors including decreased drug accumulation, reduced drug-target interactions, increased populations of cancer stem cells, enhanced autophagy activity, and reduced apoptosis in cancer cells. Reprogramming tumor cells to undergo drug-induced apoptosis provides a promising and powerful strategy for treating resistant and recurrent neoplastic diseases. This can be achieved by downregulating dysregulated antiapoptotic factors or activation of proapoptotic factors in tumor cells. A major target of dysregulation in cancer cells that can occur during chemoresistance involves altered expression of Bcl-2 family members. Bcl-2 antiapoptotic molecules (Bcl-2, Bcl-xL, and Mcl-1) are frequently upregulated in acquired chemoresistant cancer cells, which block drug-induced apoptosis. We presently overview the potential role of Bcl-2 antiapoptotic proteins in the development of cancer chemoresistance and overview the clinical approaches that use Bcl-2 inhibitors to restore cell death in chemoresistant and recurrent tumors.